Decellularized Adipose Matrix Rejuvenates Photoaged Skin through Immune Microenvironment Modulation - Jialiang Zhou; Shengjie Jiang; Liyun Wang; Kaili Lin; Jianyong Wu; Haijun Gui; Zhen Gao (BME Frontiers, 2025)
Objective: This study aims to explore the therapeutic potential of decellularized adipose matrix (DAM) in rejuvenating photoaged skin by modulating the immune microenvironment. Impact Statement: DAM effectively induces M1 to M2 macrophage polarization and rescues the function of photoaged fibroblasts through paracrine mechanisms, providing a novel strategy for skin antiaging through immune microenvironment remodeling. Introduction: Photoaging, triggered by prolonged ultraviolet exposure, is marked by the depletion of skin structural elements and a persistent inflammatory environment. Current clinical interventions primarily target structural defects, while immune modulation remains underexplored. Therefore, developing biomaterials with both extracellular matrix (ECM) replenishment and immune regulatory functions is crucial for skin regeneration. Methods: A photoaged mouse model was established using ultraviolet B irradiation to validate the inflammatory microenvironment. DAM was prepared via physicochemical decellularization and assessed in vitro for its effects on macrophage polarization and macrophage-fibroblast cross-talk. A DAM-functionalized hyaluronic acid (HA/DAM) hydrogel was developed and evaluated for its effects on skin rejuvenation via subcutaneous injection. Results: In vitro experiments demonstrated that DAM substantially promoted M2 macrophage polarization, and M2-macrophage-conditioned medium further improved fibroblast functions, including oxidative stress resistance, migration, and ECM synthesis. In vivo, HA/DAM hydrogel not only increased dermal thickness and collagen density but also restructured the immune microenvironment through M2 macrophage polarization. Conclusion: DAM offers a novel therapeutic approach for skin rejuvenation by modulating the immune microenvironment, demonstrating notable clinical potential.